ANALISIS SWOT: FAKTOR INTERNAL DAN EKSTERNAL PADA PENGEMBANGAN USAHA KANTIN DI KAMPUS UNIVERSITAS PAPUA - Venesia Yunita Patipari; Diana N. Irbayanti; Ardha Puspita Sari (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2020)
The processing industry is an industry that processes raw products into semi-finished or finished products. Such as the food, beverage, wood processing, printing and others industries. Generally, the processing industry is run and controlled by SMEs. In West Papua, the number of MSEs continues to increase from year to year. The development of the canteen business on campus is one of the micro and small businesses that is quite promising with its market share being students, lecturers and also administrative staff in the campus environment. One of the campuses that has a canteen is the University of Papua. The University of Papua is the only State University in West Papua, so it has a large number of students and employees (lecturers and staff) and will continue to grow every year. In 2020, the number of students and as many as 8,459 people and 694 lecturers spread across 12 main faculties in Manokwari Regency. This study aims to determine the external and internal conditions of the canteen business at UNIPA and also to determine the development strategies that can be applied by the canteen business at UNIPA. The research took place from 03 July 2020 to 18 July 2020. The implementation site was carried out at the Papua University Campus (UNIPA), Manokwari Regency. The method used is descriptive method. Subjects in the study were canteen entrepreneurs at the UNIPA campus. Be it business actors and HMJ. Purrosive sampling method. The data collected in this study are primary data and secondary data. The data analysis used in this study was processed and tabulated and then analyzed with a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The internal conditions faced by the canteen business are illustrated by the total score on the IFE and EFE matrices. The total internal factor is 3.83 and the external total factor is 3.99. The IE matrix is prepared by plotting the total weighted average score of the IFE matrix on the x-axis and EFE on the y-axis. The evaluation results of the IFE matrix show a value of 3.83 which illustrates the strong internal conditions of the canteen business. Meanwhile, the evaluation results of the EFE matrix show a value of 3.99 which describes the external conditions of the canteen business which are quite strong.